Chemical reservoirs and convection in the Earth's mantle - Introduction - Davies, J; Brodholt, J; Wood, B (2002)
On 16 and 17 January 2002 The Royal Society held a meeting to discuss one of the most contentious issues in the Earth sciences, which has generated heated debate between scientists studying the Earth's interior for the last 20 years or so. In its simplest and earliest form the debate centred on whether the Earth's upper and lower mantles are mixing. Several compelling geochemical arguments required (at least) two distinct mantle reservoirs that have preserved chemical heterogeneity for billions of years. The boundary between the two reservoirs has traditionally been placed at 670 km from the Earth's surface, the depth where the major phase transition of ringwoodite to perovskite and magnesiowustite may act to impede flow. Recent seismological studies, however, provide what seems to be overwhelming evidence that some subducting slabs do penetrate deep into the lower mantle (i.e. deeper than 670 km) and thereby directly contradict the model of geochemically isolated upper and lower mantles. This evidence seems so strong that, in fact, nobody at this Discussion Meeting seriously proposed that the simple model of separately convecting isolated upper and lower mantles is appropriate for today's Earth (although Professor McKenzie, during a discussion period, did give a word of warning that the tomographic images only show seismically fast areas: they do not in themselves give direct evidence for mass transport). Although the simple model of two-layered convection appears (for the moment at least) to be out of favour, many of the arguments that supported it are still difficult for a whole-mantle-convection model to explain. Plenty of exciting alternative scenarios were presented at the meeting.